Elaboración de un bioproducto a partir de sustratos lignocelulósicos y micelio de Pleurotus ostreatus alterno al poliestireno expandido (2023)
The production of biomaterials based on microbial growth has become one of the alternatives with the greatest potential in mitigating adverse effects on the environment, being widely reported as alternatives to materials such as expanded polystyrene. This project focused on the recovery of solid waste, with malt bran being the protagonist; Obtaining a biomaterial from mixtures of lignocellulosic substrates and Pleurotus ostreatus mycelium was studied, observing within the results a homogeneous and complete fungal colonization with the mixture of 75% malt bran and 25% wheat bran in 15 days of incubation. ; Thus, finally, the degradation of the biofilms was qualitatively evaluated under the ASTM D-5988 and ASTM D-6400 standards, identifying the partial disintegration of these in a period of 48 h, where a decrease in size from day 1 was confirmed. until the final evaluation time, comparing with other authors where biodegradability occurs in a maximum period of 2 months.